Synthesis of dimerate esters by solvent-free method - Yeong, Shoot Kian (2020)
Dimerate ester is normally used as lubricant base stock. Herein, we highlighted the preparation of several C36 dimerate esters derived from C36 dimer acid and medium chain length alcohols, i.e. 1-octanol, 1-hexanol and 2-ethylhexanol without the need for either solvent or catalyst but drying agent, 3Å molecular sieve (3Å MS) having acid value as low as 0.06 mg KOH g-1 of sample. Optimisation of various reaction parameters such as temperature, molar ratio, reaction time and water removal set-up was also carried out. The most affecting factors in synthesising low acid value C36 dimerate ester are reaction temperature and efficiency of water removal. The esterification was carried out under optimum conditions by refluxing at 200°C for 24 hr using 1:4.5 molar ratio of C36 dimer acid/alcohol in the presence of 15% w/w of 3Å MS.